Analysis of banana transcriptome in banana roots in response to infection by tropical race 4 of Fusarium oxysporum f. sp. cubense - Munusamy, Umaiyal; Mohd Yusuf, Yusmin; Baharum, Nadiya Akmal; Zaidi, Kamilatulhusna; Abdullah, Siti Nor Akmar; Othman, Rofina Yasmin (Institute of Plantation Studies, Universiti Putra Malaysia, 2017)
Pisang Berangan, is the most popular dessert banana cultivar in Malaysia. This AA type is grouped within highly nutritious type of fruits. Therefore, its production to cater for human needs is crucial. However, fusarium wilt disease is threatening world banana production. Availability of banana transcriptome will be highly useful for improving banana gene annotation and for biological research. The knowledge of global gene expression patterns that are influenced by the Fusarium races, the varieties of infected banana cultivar and the environmental conditions will help to provide better understanding on the host responses towards the infection. RNA samples from laboratory infected Berangan were pooled for transcriptomics using the Illumina Technology. Analysis of the banana transcriptome led to the identification of overexpressed genes. Differential gene expression (DGE) profiling analysis reveals that the infection by Fusarium caused changes in the global gene expression profiles in the banana roots 2 hrs post infection. The infection led to the induction of many well known defense related genes. This transcriptome profiling analysis indicates that early detection is possible and through this any infected plant can be identified and further essential precaution can be carried out.